Implementation of Fetal Clinical Exome Sequencing: Comparing Prospective and Retrospective Cohorts. Issue 8 (August 2022) - Marangoni, Martina; Smits, Guillaume; Ceysens, Gilles; Costa, Elena; Coulon, Robert; Daelemans, Caroline; De Coninck, Caroline; Derisbourg, Sara; Gajewska, Kalina; Garofalo, Giulia; Gounongbe, Caroline; Guizani, Meriem; et al.
Abstract : (Abstracted from Genet Med 2022;24:344–363) Approximately 2% to 3% of pregnancies are affected by fetal abnormalities, and many of these are detected by ultrasound. After identification of suspected fetal structural anomaly, invasive procedures such as chorionic villus sampling and amniocentesis are offered as a method of prenatal genetic diagnosis.